2009
DOI: 10.1016/j.vetpar.2009.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and transmission of Hepatozoon canis (Apicomplexa: Hepatozoidae) by the tick Amblyomma ovale (Acari: Ixodidae)

Abstract: The present study aimed to evaluate under controlled conditions the acquisition of Hepatozoon canis by Amblyomma ovale after feeding on infected dogs, and the subsequent induction of infection in uninfected dogs that ingested the experimentally infected ticks. Two H. canis naturally infected dogs were infested with A. ovale adult ticks derived from an uninfected laboratory tick colony. After feeding, two A. ovale females presented H. canis oocysts in the hemolymph at the first and fourth days after removal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 19 publications
1
49
2
2
Order By: Relevance
“…In the present study, the species R. sanguineus was only identified in one of the dogs evaluated, and no other tick species were identified. This is not a conclusive finding with regard to participation of the species R. sanguineus in the transmission of hepatozoonosis, even though this possibility was previously pointed out by Forlano et al (2005), Baneth et al (2007), and Rubini et al (2009).…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…In the present study, the species R. sanguineus was only identified in one of the dogs evaluated, and no other tick species were identified. This is not a conclusive finding with regard to participation of the species R. sanguineus in the transmission of hepatozoonosis, even though this possibility was previously pointed out by Forlano et al (2005), Baneth et al (2007), and Rubini et al (2009).…”
Section: Discussioncontrasting
confidence: 57%
“…This has motivated use of molecular biology techniques in studies on the etiology and epidemiology of canine hepatozoonosis. Several authors like Inokuma et al (2002), Forlano et al (2005), Spolidorio et al (2009) have used PCR to identify these agents. As already mentioned, PCR reactions performed on two samples obtained in this study confirmed the presence of Hepatozoon sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O parasitismo de Amblyomma ovale nos cães de áreas peri-rurais do munícipio de Rio Branco, AC, os predispõem a serem acometidos por hepatozoonose canina uma vez que Rubini et al (2009) afirmam que A. ovale é o vetor potencial de hepazoonose em cães rurais. Além do mais, Sousa et al (2017) verificaram a alta prevalência de Hepatozoon entre carnívoros amostrados no Pantanal e a ocorrência de infestação de A. ovali em animais silvestres.…”
Section: Resultsunclassified